2006
DOI: 10.1002/bdd.485
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a novel histone deacetylase inhibitor, apicidin, in rats

Abstract: This study is the first report of the pharmacokinetics of a novel histone deacetylase inhibitor, apicidin, in rats after i.v. and oral administration. Apicidin was injected intravenously at doses of 0.5, 1.0, 2.0 and 4.0 mg/kg. The terminal elimination half-life (t1/2), systemic clearance (Cl) and steady-state volume of distribution (Vss) remained unaltered as a function of dose, with values in the range 0.8-1.1 h, 59.6-68.0 ml/min/kg and 2.4-2.7 l/kg, respectively. Whereas, the initial serum concentration (C0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…In our pervious study, however, no saturable disposition was observed over the i.v. dose range of 0.5-4.0 mg/kg (Shin et al, 2006). The serum concentrations obtained after oral administration of 5 or 10 mg/kg in our present study were within the ranges of the observed serum concentrations in our previous study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In our pervious study, however, no saturable disposition was observed over the i.v. dose range of 0.5-4.0 mg/kg (Shin et al, 2006). The serum concentrations obtained after oral administration of 5 or 10 mg/kg in our present study were within the ranges of the observed serum concentrations in our previous study.…”
Section: Discussionsupporting
confidence: 89%
“…One of the sites responsible for potential extrahepatic metabolism is the lung (Heinemann and Fishman, 1969). The total systemic clearance of apicidin in conscious rat was reported to be 15.7 ml/min (Shin et al, 2006), which was significantly higher than the liver blood flow (11.9 ml/min) (Bernareggi and Rowland, 1991). The role of biliary and urinary excretion of apicidin seems to be minor as well (Shin et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations